Implementation Principles of the Project Management by a Security Systems Design - Reitspis, Josef; Kormancova, Gabriela (Communications - Scientific letters of the University of Zilina, 2008)
The project management includes acomplicated complex of activities. An important component of these activities is technical use of software for the support of project management and the management of the object, service (or their combination), which are outputs of the project. The important group of the activities creates the management of the cost with the accent on complex project efficiency. The next activities are connected with the management of the processes in the time, their coordination and their following communication among various participants of the project. There are many specialized activities in the life-cycle of the project, and for this reason the project manager must have abroad and complex area of special knowledge. He should improve not only in the area of his competences and skills but also in the area in which he works (in various economic areas or in the security area).